CARTOGRAPHIE DES ZONES POTENTIELLES DE RECHARGE DES EAUX SOUTERRAINES DU PALEOCENE SUPERIEUR PAR LA METHODE MULTICRITERE DANS LE BASSIN DU MONO-COUFFO AU BENIN - VISSIN, EXPÉDIT WILFRID (My University, 2019)
Estimating recharge is essential for the proper management and protection of groundwaterresources. The integration of Geographic Information Systems (GIS) techniques isknown as a robust technique for mapping the vulnerability of groundwater. The recharge of aquifersis more a function of the combinedeffects of climate, hydrogeologicalparameters, soilmoisture, topography, surface conditions and water extraction thantheir simple influence. This study deals with the vulnerability of Paleoceneaquifers in the Mono-Couffo basin, located in the MonoCouffodepartment. A mapping of potential recharge areas wascarried out using GIS and RemoteSensing techniques. It emergesfromthisstudythat the main factors in the recharging process are:lithology; fracturing, hydrographic network, slope and land use. The weighting and the combination of thesefactors made it possible to determinethat the veryweakpotential recharge zones are to the NE, SE and NW of the zone and represent 30.60% of the area of the study zone observed in the regions of Houéyogbé, Agbodji and Tohou. On the other hand, the high and very high potential recharge areas represent 26.45% of the total area of the study area. The zones withmoderatepotential, meanwhile, occupy 39.25% of the total area and mark the transition between the zones verylow to lowpotential and those high to very high.
Keywords: Cartography; Refill post area; aquifer; Upper Paleocene; Mono-Couffo